Post COVID-19 Effects on Human Health - Padilla-Raygoza, Nicolás (IntechOpen, 2023)
This book discusses post-COVID health conditions, ranging from mental health issues to central nervous system complications. It also examines prevention strategies such as vaccination and early treatments. There is also a chapter dedicated to the pandemic in Latin America and Mexico, where socioeconomic inequalities may exacerbate the health complications of the virus. This volume is a valuable resource for public health decision-makers and other interested readers.